Carotenoids in the cells of the alga Trentepohlia gobii Meyer - Bazyli Czeczuga; Oleg M. Maximov (Acta Societatis Botanicorum Poloniae, 2014)
Column-, and thin-layer chromatography revealed the presence of the following carotenoids in the cells of the species Trentepohlia gobii Meyer from cobbles in the river Urmi in the Badzhal mountains of Khabarovsk Territory in the Far East: ß, ß-carotene, ß, ε-carotene, ß, ß-carotene-2-ol, ß, ε-carotene-2-ol, ß, ß-carotene-2, 2'-diol, 5,6-epoxy-5,6-dihydro-ß, ß-carotene-2-ol, 5,6-epoxy-5,6-dihydro-ß, ε-carotene-2-ol and 5,6,5',6'-diepoxy-5,6,5',6'-tetrahydro-ß, ß-carotene-2,2'-diol.